Making advances - Vanson, Yvette ([S.l.] : Vanson Wardle [production company] ; London : BBC Training Videos [distributor])
The aim of the video is to help identifying sexual harassment, to understand its implications, and to assist in developing policies and strategies to combat it.
part 1 Myths, males and myopia - part 2 Naming the beast - part 3 Paying the price
Copy available in DVD format
Writer, Tony Wardle
Presenter: Emma Freud
Keywords: Sexual harassment of women; Sex in business; Women -- Employment